Helminth Sensing at the Intestinal Epithelial Barrier—A Taste of Things to Come - Faniyi, Aduragbemi A.; Wijanarko, Kevin J.; Tollitt, James; Worthington, John J. (Frontiers in Immunology, 2020)
Human intestinal helminth infection affects more than 1 billion people often in the world's most deprived communities. These parasites are one of the most prevalent neglected tropical diseases worldwide bringing huge morbidities to the host population. Effective treatments and vaccines for helminths are currently limited and therefore it is essential to understand the molecular sensors that the intestinal epithelium utilizes in detecting helminths; and how the responding factors produced act as modulators of immunity. Defining the cellular and molecular mechanisms that enable helminth detection and expulsion will be critical in identifying potential therapeutic targets to alleviate disease. However, despite decades of research, we have only recently been able to identify the Tuft cell as a key helminth sensor at the epithelial barrier. In this review, we will highlight the key intestinal epithelial chemosensory roles associated with the detection of intestinal helminths, summarizing the recent advances in Tuft cell initiation of protective type 2 immunity. We will discuss other potential sensory roles of epithelial subsets and introduce enteroendocrine cells as potential key sensors of the microbial alterations helminth infection produces, which given their direct communication to the nervous system via the recently described neuropod, have the potential to transfer the epithelial immune interface systemically.